Formulasi Sediaan Pengharum Ruangan Dari Minyak Melati Dengan Minyak Akar Wangi Sebagai Pengikat - Surbakti, Christica Illsanna; Swadana, Eka (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2018)
Fragrance is a growing product today, one of which is in the form of air freshener. Fragrance materials used in the product are divided into two types, namely synthetic deodorizer and natural fragrance. Synthetic deodorizer has a sharper fragrance, so it can cause dizziness, while natural fragrance has a softer fragrance.The selection of gel form is because it is more durable and practical in use. Purpose: The purpose of this study for formulate carrageenan and natrium alginat as a base of gel air freshener, for formulate jasmine oil with the various concentration as a fragrance, for formulate vetiver oil with the various concentration as a fixative Methods: This research consist of three stages. First, looking for the best base of gel air freshener by using combination of carrageenan and natrium alginat with three percent concentration at many comparison, they are 70:30, 60:40, 40:60, 30:70. And then, looking for the best fragrance by using rose oil at many concentration. They are 1%, 2%, 4% dan 6%. And then, looking for the best concentration of vetiver oil that can endurance the fragrance of jasmine oil for the longest time on storage in different place, such as AC room and fan room. Results: The results of this study indicate that the best gel formulation are mixture carrageenan and natrium alginat with comparison 70:30. The best fragrance of jasmine oil is eight percent concentration. The longest fragrance endurance is vetiver oil with one percent concentration. Conclusion: Combination of carrageenan and natrium alginat with comparison 70:30 can be formulated as a base of gel air freshener, the best concentration of jasmine oil is four percent, and the best concentration of vetiver oil is one percent